Association of Plasma KIM-1, TNFR-1, and TNFR-2 With Cardiovascular Outcomes and All-Cause Mortality in Individuals With Chronic Kidney Disease: An Ancillary Analysis of SPRINT - Nicholas Wettersten; Ronit Katz; Simon B. Ascher; Rebecca Scherzer; Alexander L. Bullen; Teresa K. Chen; Kasey Campos; Pranav S. Garimella; Michelle M. Estrella; Michael G. Shlipak; Joachim H. Ix (Kidney Medicine)
Rationale & Objective: Among individuals with chronic kidney disease (CKD), higher blood levels of kidney injury molecule-1 (KIM-1) and soluble tumor necrosis factor receptors (TNFR-1 and TNFR-2) have been associated with greater risk of CKD progression. Their associations with risk of cardiovascular disease (CVD) and all-cause mortality in individuals with CKD remain uncertain. Study Design: An observational cohort study. Setting & Participants: Systolic Blood Pressure Intervention Trial participants with hypertension and CKD (eGFR <60 mL/min/1.73 m2) but without diabetes. Predictors: Plasma KIM-1, TNFR-1, and TNFR-2. Outcomes: A composite CVD outcome (acute coronary syndrome/myocardial infarction, stroke, heart failure, and CVD death) and all-cause mortality. Analytic Approach: Cox proportional hazards models, adjusting for CVD risk factors, eGFR, and urine albumin-to-creatinine ratio. Results: Total of 2,350 participants with a mean age of 73 ± 9 years, eGFR of 46 ± 10 mL/min/1.73m2 and 25% prevalence of CVD. Over more than 3 years follow-up, 293 CVD events (12%) and 160 deaths (7%) occurred. Higher KIM-1, TNFR-1, and TNFR-2 were associated with higher risk of the composite CVD outcome after adjusting for CVD risk factors, but associations were no longer significant after adjusting for eGFR and urine albumin-to-creatinine ratio (KIM-1: HR = 1.13, 95% CI, 0.99-1.30; TNFR-1: HR = 1.03, 95% CI, 0.72-1.46; TNFR-2: HR = 0.98, 95% CI, 0.76-1.26). In contrast, in fully adjusted models, higher plasma KIM-1 and TNFR-1, but not TNFR-2, were associated with higher risk of all-cause mortality (KIM-1: HR = 1.23, 95% CI, 1.01-1.49; TNFR-1: HR = 2.09, 95% CI, 1.14-3.83; TNFR-2: HR = 1.19, 95% CI, 0.85-1.66). Limitations: No individuals with diabetes or stroke. Conclusions: In individuals with hypertension and nondiabetic CKD, associations of higher plasma KIM-1, TNFR-1, and TNFR-2 concentrations with CVD events were not independent of eGFR and albuminuria, whereas higher levels of plasma KIM-1 and TNFR-1 were independently associated with greater risk of all-cause mortality. Plain-Language Summary: Blood levels of kidney injury molecule-1 (KIM-1) and soluble tumor necrosis factor receptors (TNFR-1 and TNFR-2) have been associated with progression of kidney disease. We evaluated if these biomarkers were associated with risk of cardiovascular events and all-cause mortality in individuals without diabetes with hypertension and chronic kidney disease from the Systolic Blood Pressure Intervention Trial adjusting for relevant risk factors and biomarkers. We found none of the biomarkers were associated with risk of cardiovascular events, whereas KIM-1 and TNFR-1 were associated with risk of all-cause mortality. These findings suggest KIM-1 and TNFR-1 may be useful for risk prediction and emphasize the importance of inflammation as a risk factor for mortality.